PROPOSED MARKETING STRATEGY (CASE ON MEJABUNDAR STUDIO) (The Indonesian Journal of Business Administration, 2019)
With the rapid development of information technology today. Make it easier for a business to get information about a product or service that they want to use for their business needs to grow. This will lead to a problem where a service company cannot reach their customer in this era. This will cause fluctuations sales of services provided each month for the company. This is what happened to Mejabundar studio, a motion graphic studio from Bandung that cannot maximize their marketing strategy to reach consumers for stabilizing the number of projects each month. With the ease of use of social media and the development of media content, it has become one of the opportunities for MejaBundar to optimize their online channels. To generate new marketing strategy that fitted, the author uses the results of TOWS analysis from internal and external factors. The strategy generated are Promotional Strategy, Social Media Strategy, Customer Experience Strategy, Collaboration, Market Development Strategy, lastly, Product and services. This study generated an output in the form of a new marketing strategy to solve problems from MejaBundar Studio.Keywords: marketing strategy, TOWS analysis, service company, fluctuations sales, motion graphic studio